Spectrum mining of immune checkpoint inhibitor-related cutaneous toxicities and analysis of associated factors based on FAERS - Ma, Siyao (Frontiers in Pharmacology, 2026)
ObjectiveThe study sought to delineate the cutaneous toxicity spectrum of immune-checkpoint inhibitors by using the US FDA Adverse Event Reporting System, and to qualify association with other immune-related adverse events (irAEs).MethodsDisproportionality analyses relied on Reporting Odds Ratio (ROR), Bayesian Confidence Propagation Neural Network (BCPNN) and proportional reporting ratio (PRR). Univariable and multivariable logistic regression were then applied to identify other irAEs that predicted irAE-Cutaneous.Results(1) Most reports involved men aged >65 years. (2) Toxicity spectrum and outcomes: Most reports involved men over 65. Five drugs showed positive signals via the three algorithms. Immune-mediated dermatitis had the strongest signals across all. Ipilimumab strongly linked to vitiligo (ROR = 45.531); nivolumab (ROR = 9.656) and pembrolizumab (ROR = 8.376) to psoriasiform dermatitis; tislelizumab to acquired epidermolysis bullosa (ROR = 8.376). Rash and pruritus were common but weakly specific. Pembrolizumab had highest RORs for toxic epidermal necrolysis (ROR = 4.384) and Stevens-Johnson syndrome (ROR = 3.599). Nivolumab had most severe event reports, then pembrolizumab. (3) Association with other irAEs: Univariable analysis linked pneumonitis, hyperthyroidism, myositis, fatigue, hypothyroidism to skin irAEs (all P < 0.05); multivariable analysis found hyperthyroidism, myositis, fatigue, hypothyroidism as independent predictors (P < 0.05).ConclusionDistinct toxicity spectra of each drug were observed. Hyperthyroidism, myositis, fatigue and hypothyroidism independently increase the likelihood of irAE-Cutaneous.